Diagnostic of tractors and agricultural implements in the municipality of Atlacomulco, State of Mexico - Gutiérrez-Rodríguez, Francisco; Hernández Ávila, Jesús; González Huerta, Andrés; De Jesús Pérez López, Delfina; Serrato Cuevas, Rodolfo; Laguna Cerda, Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
The present investigation has like objective, the realization of a diagnostic of the utilization of the park of machines and tractors, as well as the indexes of agricultural mechanization of 24 communities of the municipality of Atlacomulco, give to know the state of these mechanized means, with the purpose that at the level of the State of Mexico the necessary measures are taken to improve the park of machines and tractors in this municipality. The 2014 and 2015 information was supported in a survey; and the sample size had a confidence level of 95% and an error limit of 9%. 140 farmers, owners of tractors were interviewed and 163 tractors were registered in an area of 8 074 ha (49.53 ha tractor-1). The FAO recommends 50 ha tractor-1 surface with machinable potential. It is emphasized that the tractor implement relation is quite low (1:3.4), which indicates the non-existence of a full use of the tractor and its implements during the agricultural cycle, since the hectare tractor ratio is 12.4 ha tractor-1 cultivated soil, quite low figure, taking into account the average power per agricultural tractor. The index of energy equipment per hectare of cultivated land was 0.89 kW ha-1, a value higher than recommended by other studies. The correlation between the energy index of one hectare (ξha) and the number of tractors per 100 ha (ЭN) was r= 0.81**; also ЭN and hectares cultivated by tractor (ϕt), had a value of r= -0.63**.